2010
DOI: 10.1111/j.1462-2920.2009.02085.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of genome evolution in facultative symbionts of aphids

Abstract: Aphids are sap-feeding insects that host a range of bacterial endosymbionts including the obligate, nutritional mutualist Buchnera plus several bacteria that are not required for host survival. Among the latter, ‘Candidatus Regiella insecticola’ and ‘Candidatus Hamiltonella defensa’ are found in pea aphids and other hosts and have been shown to protect aphids from natural enemies. We have sequenced almost the entire genome of R. insecticola (2.07 Mbp) and compared it with the recently published genome of H. de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
95
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 51 publications
0
95
1
Order By: Relevance
“…Several indicators reveal that the R. insecticola 5.15 genome sequence is near completion. First, the genome size of R. insecticola 5.15 (at 2.01 Mbp) is similar to the previously sequenced R. insecticola LSR1 (at 2.07 Mbp) (Degnan et al 2010; Table 2). Second, the retrieved contigs included 186 of 205 single-copy genes (SICO) that are present in most Gammaproteobacteria (Lerat et al 2003).…”
Section: Genome Sequencing and Annotationmentioning
confidence: 59%
See 1 more Smart Citation
“…Several indicators reveal that the R. insecticola 5.15 genome sequence is near completion. First, the genome size of R. insecticola 5.15 (at 2.01 Mbp) is similar to the previously sequenced R. insecticola LSR1 (at 2.07 Mbp) (Degnan et al 2010; Table 2). Second, the retrieved contigs included 186 of 205 single-copy genes (SICO) that are present in most Gammaproteobacteria (Lerat et al 2003).…”
Section: Genome Sequencing and Annotationmentioning
confidence: 59%
“…A previously sequenced strain, R. insecticola LSR1 (Degnan et al 2010), is closely related to R. insecticola 5AU, and both originated from A. pisum collected in New York, USA. Preliminary assays suggested that R. insecticola LSR1 resembled R. insecticola 5AU in failing to confer any resistance to A. ervi (NA Moran, unpubl.).…”
mentioning
confidence: 99%
“…Population cage studies have shown that, in the absence of parasitoid pressure, the frequencies of H. defensa and S. symbiotica decrease, suggesting that infection with these symbionts imparts a cost to the aphid [26]. The recently completed genome sequences of H. defensa and R. insecticola revealed the absence of most EAA biosynthesis pathways, implying that these symbionts obtain these nutrients from the aphid's free amino acid pool [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of genome sequences, H. defensa and R. insecticola are only able to produce the essential amino acids lysine and threonine (Degnan et al, 2009a, b), but other essential amino acids also increase because of infection with these symbionts. One possibility is that facultative symbiont infection somehow stimulates Buchnera to produce amino acids, as Buchnera is the only organism in the system capable of producing most essential amino acids (Shigenobu et al, 2000).…”
Section: Metabolic Responses To Symbiont Infectionmentioning
confidence: 99%
“…Another possibility is that proteases produced by facultative symbionts are degrading proteins, increasing free amino acid pools in pea aphids. The H. defensa and R. insecticola genomes possess several proteases that could be responsible for this effect (Degnan et al, 2009a, b).…”
Section: Metabolic Responses To Symbiont Infectionmentioning
confidence: 99%